Combined impacts of climate and socio-economic scenarios on irrigation water availability for a dry Mediterranean reservoir - Nunes, João Pedro (2020)
The impacts of climate and associated socio-economic changes on water availability, including supply and demand, quality, and storage volume, were evaluated for the Vale do Gaio reservoir in southern Portugal, located in a dry Mediterranean climate and already under drought stress. The SWAT model was applied with 6 scenarios for 2071-2100, involving two storylines (A1B and B1) with individual changes in climate (-9% rainfall, increasing in winter by +28 to +30%), socio-economic conditions (an increase in irrigation demand by 11%, and a replacement of cereals and pastures by sunflower), and a combination of both. Most future scenarios resulted in lower water availability, due to lower supply (-19 to -27%) combined with higher irrigation demand (+3 to +21%). This resulted in more years with limited irrigation supplies (presently: 28%; scenarios: 37 to 43%), although limitations were mitigated by lower losses to excess discharge. Land-use changes also decreased quality by increasing P concentrations (+29 to +93%). Impacts were more severe in scenario A1B than in B1, and in combined changes than in climate or socio-economic changes only. Water availability was resilient to climate change, as impacts led only to a moderate aggravation of present-day conditions. Lower future water availability could be addressed by supply and demand management strategies and, in the most extreme scenario, by water transfers from regional water reserves; water quality issues could be addressed through land-use policies. Results also highlighted the importance of taking the characteristics of water supply systems into account when designing adaptation measures for future changes.